Should we Accept the Idea of Incorporating A CPA firm - د.محمد الهادي بعيو (Dirasat in Economics and Business, 1973)
The article provides the pros and cons of incorporating a CPA com. The writer implicitly accepts this idea and supports his opinion. Several points are discussed. These include : the accountants? legal liability, tax considerations, and other advantages of incorporation. The Legal Liability of the Accounting Profession : The legal liability of the accounting profession is a complex problem for accountants and lawyers as well. Investigation of liability cases indicates that the Court of Appeal has often reversed or altered the decisions of lower Courts. The complexity of this problem is due to the nature of the accountant's liability. The accountant is not only liable to his client, but also to the third party with whom he has no contractual relationship. In principle, the accountant is liable to the third party for gross negligence. Most people think that the unlimited liability is an indispensable aspect of the accounting profession. The writer believes, however, that this aspect has been added merely in imitation of other professions. There is evidence that unlimited liability has been disregarded in most of these professions. The writer raises the question about relieving the